1983
DOI: 10.1002/em.2860050308
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome aberrations and sister chromatid exchanges in styrene‐exposed workers with reference to their smoking habits

Abstract: The incidences of chromosome aberrations and the frequencies of sister chromatid exchanges (SCE) were investigated in cultured lymphocytes of 18 styrene-exposed workers in comparison with six controls. There was a marginal increase in the incidence of structural chromosomal aberrations in first-division metaphases in the styrene-exposed workers, as compared with the nonexposed controls. However, there was no difference in SCE frequencies. When each group was divided into smokers and nonsmokers, styrene-exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…However, other workers who have studied solvent-exposed cohorts have noted that the combination of smoking and solvent exposure may be genotoxic. In 18 workers Watanabe et al [1983] noted a significant elevation in SCE frequency in the smokers exposed to styrene, while the SCE level in the non-smoking workers was not different than controls. Fredga et al [1982] observed that the SCE frequency in fuel-exposed personnel who smoked was above similar controls, while the non-smoking, exposed workers had SCE levels essentially similar to non-smoking controls.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, other workers who have studied solvent-exposed cohorts have noted that the combination of smoking and solvent exposure may be genotoxic. In 18 workers Watanabe et al [1983] noted a significant elevation in SCE frequency in the smokers exposed to styrene, while the SCE level in the non-smoking workers was not different than controls. Fredga et al [1982] observed that the SCE frequency in fuel-exposed personnel who smoked was above similar controls, while the non-smoking, exposed workers had SCE levels essentially similar to non-smoking controls.…”
Section: Discussionmentioning
confidence: 80%
“…Haglund et al [ 19801 completed [Toftgard and Gustafsson, 19801, elevations in SCE attributable to recent exposure (within weeks) may have gone undetected in both studies. Bias of this sort (misclassification) might also explain the lack of consistency between studies in the detection of an increase of SCE in smoking workers (an elevation in SCE similar to that reported by Fredga et al [1982], Maki-Paakkanen et al [1984], and Watanabe et al [1983]). …”
Section: Discussionmentioning
confidence: 92%
“…Six out of 20 exposed workers were smokers, with a mean consumption o f eight (ran ge [3][4][5][6][7][8][9][10][11][12][13] cigarett es per day. Eleven out of 22 referents were smo kers, with a mean consumption of 12 (range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] cigar ettes per da y. Of th e exposed subjects 13 had had radiographic examinations du ring the last year, and th ree regularly took drug s (theophyllin, terbutalin, pidolol , insulin).…”
Section: Subjects and Samplingmentioning
confidence: 99%
“…It has been shown that concomitant exposure to aromatic solvents and polycyclic aromatic hydrocarbons (PAHs) in cigarette smoke and combustion emissions may result in a toxic interaction between these two xenobiotics (Watanabe et al, 1983). In epidemiologic studies, petroleumprocessing industry workers had a higher incidence of both sister chromatid exchange (SCE) and chromosomal aberrations in lymphocytes (Simenova et al, 1989), while solvent-exposed smoking painters had high levels of lymphatic SCE (Kelsey et al, 1989).…”
mentioning
confidence: 99%